A comparative study of serum electrolytes and lipid levels in ischaemic and haemorrhagic stroke - Wali, Vinod V.; Patil, Smita S. (International Journal of Research in Medical Sciences, 2016)
Background: Stroke or cerebrovasular accident is a major cause of disability worldwide and the second most common cause of death after ischaemic heart disease. There has been a steady increase in incidence of stroke; recent data shows that stroke incidence decreased by 42% in high-income countries and by 100% in low to middle income countries. Aim of the study was to know the association of serum electrolytes and lipid levels in stroke. Methods: This was a retrospective study conducted in June 2014 at tertiary care hospital in South India. Data was obtained from the medical records departments from June 2011 to August 2012. An adult Treatment Panel III criterion was used to classify plasma lipid levels. The serum urea, serum creatinine, serum electrolytes and urinary electrolyte levels were measured by flame photometry. Descriptive statistics has been carried out in the present study. Student ‘t’ test used to test the significance, between the groups and P value of <0.05 were considered as moderately significant, P values of <0.01 was considered highly significant. Results: There was no statistically significant difference in electrolyte levels between ischaemic and haemorrhagic stroke patients. Most common electrolyte imbalance in ischaemic stroke was hyponatremia and most common electrolyte imbalance in Haemorrhagic stroke was hypokalemia. Statistically significant alteration were seen in total cholesterol, LDL and VLDL levels between haemorrhagic and ischaemic stroke. Conclusions: In the present study total cholesterol and HDL levels were higher in haemorrhagic stroke whereas triglycerides, LDL and VLDL were high in ischaemic stroke. Regular monitoring of lipid levels in patients with high risk factors for stroke patients will help in decreasing the mortality and morbidity. Future studies should be prospective, multi-centric and include a large sample size which will help in determining the association between electrolytes and lipid levels in stroke patients.